PENGARUH PERMAINAN EDUKATIF TERHADAP PERILAKU REMAJA PUTRI DALAM MANAJEMEN KEBERSIHAN MENSTRUASI - Triatmi Andri Yanuarini; Ulfa Pradipta; Koekoeh Hardjito (Poltekkes Kemenkes Malang, 2020)
When the adolescent girls have their period they are required to manage, their menstrual need in some material such changing sanitary pads more often during menstruation, access disposal, toilet, soap, and water to clean themselves. However, there are many adolescent girls who still having a lack behavior in Menstrual Hygiene Management. This study was a quantitative research used pre experimental designed one group pretest posttest. The sample was selected by simple random sampling with 19 adolescents as a sample. The data were collected by checklist observation and analyzed with Wilcoxon. A Statistical test in this study was shown z count equals to 3.83 is greater than z It could be concluded that Ha was accepted so, there is an influence of game based education on adolescents girl behavior in Menstrual Hygiene Management or MHM.